Effects of compaction prressure on lead zirconate titanate piezoelectric and dielectric properties prepared via high planetary mill - Bahanurddin, N.F.K.; Jumali, M.H.; Mohamed, J.J.; Ahmad, Z.A. (Hanyang University, 2015)
Lead Zirconate Titanate (PZT) had previously been used as actuators and sensors in electronic application due to its remarkable piezoelectric properties. The main obstacle in the PZT syntheses through solid state sintering is the lost of substantial amount of PbO due to vaporation that accompanied high firing temperature. Elimination of the calcination step and alternative method of treatment could be of a great help. Thus, an investigation of the lead (Pb) Zirconate Titanate PZT properties (piezoelectric and dielectric) synthesized via solid-state reaction by varying compaction pressure (100-300 MPa) was conducted. Compaction pressure that was beneficial to the physical properties of PZT-based ceramic and also effectively improved the dielectric and piezoelectric properties of the PZT ceramics. Optimum average grain size was found to be a very important factor in determining the alignment of the d33 particle size value influence and the dielectric constant of PZT. Therefore, the optimum compaction pressure (200 MPa) played an important role in optimizing the sintering temperature. This also enhanced/improved the piezoelectric and dielectric properties of PZT.